When epitaxy meets plasma: a path to ordered nanosheets arrays - Zhuang, Hao; Zhang, Lei; Fuchs, Regina; Staedler, Thorsten; Jiang, Xin (Scientific reports, 2013)
The possibility of a controlled assembly of 2-dimensional (2D) nanosheets (NSs) into ordered arrays or even more sophisticated structures offers tremendous opportunities in the context of fabrication of a variety of NSs based devices. Reports of such ordered NSs are rare and all conventional “top-down” methods typically led to coarse structures exhibiting only limited surface quality. In this work, we demonstrate a path to directly synthesis ordered NSs arrays in a plasma activated chemical vapor deposition technique utilizing planar defects formed during hetero-epitaxial growth of crystals featuring a close-packed lattice. As an example, the synthesis of 3C-SiC NSs arrays with well-defined orientation on (001) and (111) Si substrates is shown. A detailed analysis identifies planar defects and the plasma environment as key factors determining the resulting 2D NSs arrays. Consequently, a “planar defects induced selective growth” effect is proposed to elucidate the corresponding growth mechanism.